Circulating microRNAs in adrenal tumors. Issue 3 (June 2019) - Igaz, Peter
Abstract : Purpose of review: Circulating microRNAs represent promising minimally invasive markers of several diseases including tumors. As the preoperative diagnosis of different adrenal tumors is difficult, for example, diagnosis of adrenocortical or adrenomedullary malignancy, circulating microRNAs might be helpful in their clinical management. Recent findings: Observations regarding the applicability of circulating microRNAs isolated both from unfractionated plasma or serum and from extracellular vesicle preparations for the diagnosis of adrenocortical malignancy have been published. Data show that circulating microRNA might be exploited for monitoring adrenocortical cancer progression. Circulating microRNA profiles of adrenal myelolipoma have also been published that might be useful for differentiating adrenocortical cancer and adrenal myelolipoma in dubious cases. Summary: In this review, recent advances in the field of circulating microRNAs in adrenal tumors are discussed.